Activity test of various mangosteen (Garcinia mangostana) pericarp extract fractions to decrease fasting blood cholesterol levels and lipid peroxidation activity in diabetic mice - Saikhu Akhmad Husen; Dwi Winarni; Firas Khaleyla; Septian Hary Kalqutny (The East Java Biological Society, 2016)
The objectives of this study were to determine the effect of various fractions of mangosteen (Garcinia mangostana) pericarp extract to the changes of the fasting blood cholesterol and serum malondialdehyde (MDA) levels on diabetic mice (Mus musculus). Thirty 3-4 months old male mice strain BALB/c, weight 20-30 g were divided into six groups. The first group was KN as a non diabetic control group, KD as a diabetic control, KM as a group of diabetic mice treated with metformin, and NP, SP, and P as the treatment groups that were treated by using three different fractions from mangosteen pericarp extract, non polar, semi polar, and polar respectively. The induction of Diabetes mellitus was done by the injection of STZ, and the mice were given a high fat diet treatment to induce the hiperlipidemia condition using lard for three weeks. The blood cholesterol levels were measured in all groups before and after the injection of lard, and day 1, 7, and 14 of treatment as well. The serum MDA level as the indicator of lipid peroxidation were measured by using QuantiChrom TBARS Assay Kit (DTBA-100). The data of cholesterol levels were statistically analyzed by t-test, while the data of serum MDA levels were analyzed by variance analysis followed by Duncan test. The results showed that the polar fraction of mangosteen pericarp had effect to decrease the fasting blood cholesterol level in mice, however the non polar and semi polar fraction had no simmilar effect. All of the fractions has shown significant effect to decrease the serum MDA level in mice.